REPRODUCTIVE HEALTH OF WOMEN THE REPUBLIC OF KHAKASSIA AND ITS INFLUENCE ON THE DEMOGRAPHIC SITUATION - Гладкая, Валентина Сергеевна; Медведева, Надежда Николаевна; Захарова, Татьяна Григорьевна; Грицинская, Вера Людвиговна (Mother and Baby in Kuzbass, 2016)
The estimation of medical-demographic processes in the Republic of Khakassia. Studied the main demographic indicators: population, birth rate, total mortality, infant, parental and maternal, indices, characterizing and affecting the reproductive health of the population in the dynamics since 1990.
Keywords: the Republic of Khakassia; the demographic situation; reproductive health; fertility; mortality; morbidity; infertility; abortion; contraception.